DNA barcode regions for differentiating Cattleya walkeriana and C. loddigesii - Rivera-Jiménez, Hernando; Rossini, Bruno César; Tambarussi, Evandro Vagner; Ann Veasey, Elizabeth; Ibanes, Bruna; Marino, Celso Luis (Acta Scientiarum. Biological Sciences, 2017)
Growers appreciate Cattleya walkeriana and C. loddigesii due to striking shape and rarity. Thus, this study aimed to evaluate the feasibility of DNA barcode regions, namely ITS1, ITS2 and rpoC1, to discriminate between C. walkeriana and C. loddigesii species. DNA barcode regions were successfully amplified using primers designed to amplify plants. We also included sequences from public databases in order to test if these regions were able to discriminate C. walkeriana and C. loddigesii from other Cattleya species. These regions, and their combinations, demonstrated that the ITS1+ITS2 had the highest average interspecific distance (11.1%), followed by rpoC1 (1.06%). For species discrimination, ITS1+ITS2 provided the best results. The combined data set of ITS1+ITS2+rpoC1 also discriminated both species, but did not result in higher rates of discrimination. These results indicate that ITS region is the best option for molecular identification of these two species and from some other species of this genus.